THE CORRELATION OF CARDIOMEGALY AND STROKE SEVERITY: AN ANALYTICAL STUDY - Awwalia, Fildza; Rahmawati, Vita Kusuma (Journal of Pain, Headache and Vertigo, 2026)
Background: Stroke is characterized as a neurological deficit attributed to an acute injury of Central Nervous System (CNS) by a vascular cause. Cardiomegaly means enlargement of heart. Both stroke and cardiomegaly are related to vascular problems, but the correlation between them remains unclear. Objective: This study was conducted to examine risk factors related to stroke severity (based on National Institute of Health Stroke Scale) especially cardiomegaly at Lumajang Islamic Hospital in January to June 2025. Method: This study is an analytic observational study, retrospective data by using hospital medical records. Data were obtained from 124 inpatients cases admitted between January to June 2025 in Lumajang Islamic Hospital. The risk factors were studied are cardiomegaly, hypertension, diabetes mellitus, age, time of patient arrival. Results: The Pearson Chi-Square test indicated no significant correlation between cardiomegaly and NIHSS (stroke severity) with p = 0,080, nor with hypertension (p = 0,621), diabetes mellitus (p = 0,345) or age (p = 0,721). A statistically significant correlation was observed between the patient's arrival time and the severity of stroke (p = 0.000), including the arrival time of patients with cardiomegaly at the hospital (p = 0.020). Conclusion: This study demonstrated no significant correlation between cardiomegaly, hypertension, diabetes or age to stroke severity. However, significant correlation was found in patients arrival time including in cardiomegaly patients. These findings highlight the critical importance of early detection and timely medical intervention in stroke cases, particularly for patients with cardiomegaly.